Criminalizing the illegal use of debit cards (Journal of Misan Researches, 2022)
The bank card, or the reference to it was brief and limited only to the punishment of those who forged and used it, in the laws regulating these bank cards, such as the Electronic Transactions and Personal Data Law, and the Iraqi Information Crimes Draft Law, so the research on the subject of this study that we have to refer to the traditional punitive rules of offenses against the carer's money. Perhaps the importance of this study is embodied in his mind, despite the acceleration and increase in the number of dealers with this type of cards This is in light of the efforts of major banks and financial institutions to provide the best banking services to their customers by introducing electronic means in their work, especially the ATM service, which has become widespread in large numbers, especially in shopping centers. The cardholder misused it, especially in the laws on bank cards